A subset of human plasmacytoid dendritic cells expresses CD8α upon exposure to herpes simplex virus type 1 - Schuster, Philipp; Thomann, Sabrina; Werner, Maren; Vollmer, Jörg; Schmidt, Barbara (Frontiers in Microbiology, 2015)
Classical and plasmacytoid dendritic cells (DC) play important roles in the defense against murine and human infections with herpes simplex virus (HSV). So far, CD8α expression has only been reported for murine DC. CD8α+ DC have prominent cross-presenting activities, which are enhanced by murine CD8α+ PDC. The human orthologue of murine CD8α+ DC, the CD141 (BDCA3)+ DC, mainly cross-present after TLR3 ligation. We report here the serendipitous finding that a subset of human PDC upregulates CD8α upon HSV-1 stimulation, as shown by gene array and flow cytometry analyses. CD8α, not CD8ß, was expressed upon exposure. Markers of activation, migration, and costimulation were upregulated on CD8α-expressing human PDC. In these cells, increased cytokine and chemokine levels were detected that enhance development and function of T, B, and NK cells, and recruit immature DC, monocytes, and Th1 cells, respectively. Altogether, human CD8α+ PDC exhibit a highly activated phenotype and appear to recruit other immune cells to the site of inflammation. Further studies will show whether CD8α-expressing PDC contribute to antigen cross-presentation, which may be important for immune defenses against HSV infections in vitro and in vivo.